Behavior of Paussus favieri (Coleoptera, Carabidae, Paussini): A Myrmecophilous Beetle Associated with Pheidole pallidula (Hymenoptera, Formicidae) - Emanuela Maurizi; Simone Fattorini; Wendy Moore; Andrea Di Giulio (Psyche: A Journal of Entomology)
Several specimens of the myrmecophilous beetle Paussus favieri were reared in ant nests of Pheidole pallidula. Their interactions were recorded and all behaviors observed are described. Duration and frequency of five behaviors of P. favieri were analyzed with ANOVA and post hoc Tukey tests; these comprised rewarding, antennal shaking, antennation, escape, and “no contact”. Significant differences both in duration and in frequency among behaviors were detected. The main result is that the rewarding behavior, during which the beetle provides attractive substances to the host, is performed significantly more frequently than all others. This result strongly supports the hypothesis that the chemicals provided by the beetles and licked by the ants are of great importance for the acceptance and the full integration of P. favieri in the ant society. This result also suggests that, contrary to previous findings and interpretations, the myrmecophilous strategy of P. favieri is very similar to the symphilous strategy described for P. turcicus. The occasional interactions of some beetle specimens with the P. pallidula queen were recorded, illustrated, and discussed, indicating the possibility of a more complex strategy of P. favieri involving a chemical mimicry with the queen. In addition, the courtship performed by the beetle is described for the first time, together with a peculiar “cleaning” behavior, which we hypothesize functions to spread antennal chemicals over the body surfaces.